2004
DOI: 10.1103/physrevlett.93.190404
|View full text |Cite
|
Sign up to set email alerts
|

Density Profile of a Harmonically Trapped Ideal Fermi Gas in Arbitrary Dimension

Abstract: Closed form analytic expressions are derived for the density profile of a harmonically trapped noninteracting Fermi gas in d dimensions. Shell structure effects are included to leading order in 1/N , where N is the number of particles. These corrections to the local density approximation scale as δn/n ∼ N −α , where α = (1 + 1/d)/2.PACS numbers: 03.75.SsExperiments on quantum degenerate Fermi atoms have motivated a series of theoretical studies of the basic properties of zero [1,2,3,4,5,6] and finite [7] tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
(38 reference statements)
2
31
0
Order By: Relevance
“…In the case of a non-interacting gas, thanks to the duality of spatial and momentum coordinates in the harmonic oscillator Hamiltonian, n ν (k) has the same shape as the density profile n ν (x) ≡ ρ ν (x, x). Therefore, it displays a number of peaks coinciding with the number of fermions of that component [38][39][40], with the amplitude of these Friedel-like oscillations decreasing as the inverse of the number of fermions. Also for an interacting gas, it was found that in a two-species mixture the momentum distribution displays as many peaks as the number of fermions in each component [41], although this form does not correspond anymore to the real space distribution.…”
Section: Model and Quantities Of Interestmentioning
confidence: 99%
“…In the case of a non-interacting gas, thanks to the duality of spatial and momentum coordinates in the harmonic oscillator Hamiltonian, n ν (k) has the same shape as the density profile n ν (x) ≡ ρ ν (x, x). Therefore, it displays a number of peaks coinciding with the number of fermions of that component [38][39][40], with the amplitude of these Friedel-like oscillations decreasing as the inverse of the number of fermions. Also for an interacting gas, it was found that in a two-species mixture the momentum distribution displays as many peaks as the number of fermions in each component [41], although this form does not correspond anymore to the real space distribution.…”
Section: Model and Quantities Of Interestmentioning
confidence: 99%
“…Like above, we note that the TF densities (10), (12) for spherical potentials fulfill exactly the relation [40] …”
Section: The Semi-local Virial Theorem (Slvt)mentioning
confidence: 70%
“…Inserting the above into (A.5) for the density and keeping terms up to O(ζ −1 ), we obtain 12) where the smooth part is the TF density…”
Section: Appendix a Explicit Densities And Relations For Linear Potementioning
confidence: 99%
See 1 more Smart Citation
“…The high purity and the low temperature of the samples and the high resolution of the detection techniques make these systems ideal candidates for the study on the mesoscopic scale of single-level quantum properties such as shell structures in the particle density profiles [3][4][5][6][7]. In the experiments the trapped atomic gas can be fully spin-polarized and the strength and the anisotropy of the trap can be tuned to reach quasionedimensional (1D) or quasi-twodimensional (2D) configurations.…”
Section: Introductionmentioning
confidence: 99%